2020
DOI: 10.3221/igf-esis.53.20
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and analysis of reinforced concrete plate-column structure under room temperature and fire based on acoustic emission

Abstract: This paper attempts to disclose the damage mechanism of reinforced concrete plate-column structures under room temperature and fire. Several tests were carried out to record the law of crack development on the plate surface under room temperature. The infrared detection technology was adopted to observe how cracks develop under fire. The acoustic emission (AE) signals at different positions of the specimen were monitored by the AE techniques. Coupled with the macroscopic test phenomena, several characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…More precisely, Bhaskar et al showed that when the porous zone at the interface between steel and concrete (a zone whose volume depends on the surface of the reinforcement, the water/cement mass ratio and the degree of hydration) is completely filled by the corrosion products, pressures are exerted on the concrete cover and can generate cracks [3]. As shown in Figure 1, monitoring the propagation of these cracks is therefore essential to stop them from reaching critical sizes that could lead to the reduction of the bearing capacity of the concrete or reinforced concrete structure or even to its failure [4][5][6][7][8]. This research topic is still of great interest and recent studies have shown that it is possible to limit interfacial micro-cracks in concrete and its composites subjected to dynamic loads, for instance by adding fly ash and/or silica fume at a rate of a few thenths of the weight of the cement [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, Bhaskar et al showed that when the porous zone at the interface between steel and concrete (a zone whose volume depends on the surface of the reinforcement, the water/cement mass ratio and the degree of hydration) is completely filled by the corrosion products, pressures are exerted on the concrete cover and can generate cracks [3]. As shown in Figure 1, monitoring the propagation of these cracks is therefore essential to stop them from reaching critical sizes that could lead to the reduction of the bearing capacity of the concrete or reinforced concrete structure or even to its failure [4][5][6][7][8]. This research topic is still of great interest and recent studies have shown that it is possible to limit interfacial micro-cracks in concrete and its composites subjected to dynamic loads, for instance by adding fly ash and/or silica fume at a rate of a few thenths of the weight of the cement [7,8].…”
Section: Introductionmentioning
confidence: 99%